Hikmah Dzikir Dalam Perspektif Mafatih Al-Ghaib dan Tafsir Al-Misbah : (Tala’ah Interpretasi dengan Pendekatan Tafsir Interdisipliner) - Muhammad Shohib; Lailatul rif'ah; Lailatul Mas’udah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study analyzes the concept and wisdom of dhikr based on the interpretation of the book Mafātīḥ al-Ghayb by Fakhruddin ar-Razi and Tafsir al-Misbah by M. Quraish Shihab. The purpose of this study is to understand the depth of the meaning and function of dhikr through an interdisciplinary tafsir approach, and to identify its relevance in a modern spiritual and psychological context. The research method used is comparative tafsir (muqaran) to compare the two tafsirs, as well as an interdisciplinary tafsir approach that integrates disciplines such as Sufism and psychology. This study found that dhikr has an important role in growing faith (QS. Al-Anfal: 2), making the heart tremble when the name of Allah is mentioned, and as the main means of achieving peace of mind (QS. Ar-Ra'd: 28). In addition, Allah will remember His servants who do dhikr (QS. Al-Baqarah: 152). In the Qur'an, dhikr is not only interpreted as repeated utterances, but also as an awareness of God's presence in all aspects of life. Dhikr has broad dimensions, covering spiritual, psychological, and social aspects. Sufis view dhikr as a means to achieve ma'rifatullah (knowing Allah), while commentators interpret it as the instructions of the Qur'an that contain wisdom in forming the character of believers. In Sufism, dhikr is classified into three levels: oral, heart, and sir, which indicate spiritual depth in getting closer to Allah. From a psychological perspective, the practice of dhikr has been shown to have a significant positive impact on mental health, reducing stress, anxiety, and increasing emotional stability. This study concludes that dhikr is a multidimensional practice that is essential for the spiritual and psychological life of Muslims, and is a main pillar in achieving closeness to Allah swt. and peace of mind.